Classificador Fisherface Fuzzy para o reconhecimento de faces - Souza, Flávio Lima de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation is a study of the Fuzzy Fisherface method and fuzzy membership functions for recognizing faces. The traditional Fisherface method consists of two techniques of data dimensionality reduction: Principal Components Analysis (PCA) and Linear Discriminant Analysis (LDA). The method is relatively insensitive to many factors that in uence the images, such as variation in illumination and different facial expressions. In order to overcome these factors and improve recognition rates of the Fisherface method, fuzzy membership degrees are embedded in your algorithm, and they are which are calculated from the technique of k-nearest neighbors (KNN) to give the Fuzzy Fisherface method. The objective of this study is to evaluate the performance of these two methods and propose the use of a new membership function for the Fuzzy Fisherface method. The tests are conducted on two bases of facial images: Yale and ORL

A presente disserta c~ao e um estudo do m etodo Fisherface Fuzzy e das funções de pertinência fuzzy para o reconhecimento de faces. O tradicional método Fisherface e constituído de duas técnicas de reduçãao de dimensionalidade de dados: Análise de Componentes Principais (PCA) e Análise de Discriminante Linear (LDA). O método e relativamente insensível a diversos fatores que atuam sobre as imagens, como variação na iluminação e diferentes expressões faciais. A fim de superar esses fatores e melhorar as taxas de reconhecimento do método Fisherface, e incorporado ao seu algoritmo graus de pertinência fuzzy, que são calculados a partir da técnica de k-vizinhos mais próximos (KNN), dando origem ao método Fisherface Fuzzy. O objetivo deste trabalho e avaliar o desempenho desses dois métodos e propor a utilização de uma nova função de pertinência para o método Fisherface Fuzzy. Os testes são realizados em duas bases de imagens faciais: Yale e ORL
Keywords: Computação - Matemática; Modelos matematicos; Reconhecimento facial (Computação); Sistemas difusos; Biometria; Mathematical models